The study of consumer behavior towards processed squid market in Banphe, Rayong - ปฏิบัติ กิ่งกานต์; แสนแมน ภาคภูมิ; วรวัฒนะปริญญา ศักร์ระภีร์ (Journal of Rattana Bundit University, 2018)
The main aim of this research is to evaluate the consumer behavior of processed squid product which distributed and produced in Rayong province. In this study is survey research in the market where located in Banphe sub-district municipality, total 4 markets. The samples are the traveler who travelling to these markets total 400 people. Using questionnaire as a research tool. The results shown that main objective in purchasing processed squid product is buying for other or as a souvenir. By consider the shop where display the verities of products which the most souvenir preferred is processed squid than other choice. The traveler normally spend more than 1,000 Thai baht for each buying. The frequency problem was occurred after brought is the freshness. In part of determine to the relationship testing between spending cost is significant related to personal information at .05. The marketing mix, also effect to decision making process in the high level by mean is 3.98 of 5. The results were also evaluated by 4 of marketing dimension of product price place and promotion. Thus the different testing of decision making factor comparing to personal information shown significant different in gender, incomes and location at .05.